2016
DOI: 10.1152/ajprenal.00231.2015
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 1 receptor agonist protects podocytes through catalase and RhoA activation

Abstract: Drugs containing adrenocorticotropic hormone have been used as therapy for patients with nephrotic syndrome. We have previously shown that adrenocorticotropic hormone and a selective agonist for the melanocortin 1 receptor (MC1R) exert beneficial actions in experimental membranous nephropathy with reduced proteinuria, reduced oxidative stress, and improved glomerular morphology and function. Our hypothesis is that MC1R activation in podocytes elicits beneficial effects by promoting stress fibers and maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…identified MC1R as the dominant MCR in virtually all types of kidney parenchymal cells in humans and rats, including podocytes, glomerular endothelial cells, mesangial cells, and tubular epithelial cells. However, in a following study, selective MC1R agonists barely induced any cAMP response in podocytes58. The doubt on podocyte expression of MC1R as well as MC1R-mediated podocyte protection was further accentuated by the contradictory effects of MC1R agonists on proteinuria and podocyte injury observed in different animal models of glomerulopathies59.…”
Section: Discussionmentioning
confidence: 88%
“…identified MC1R as the dominant MCR in virtually all types of kidney parenchymal cells in humans and rats, including podocytes, glomerular endothelial cells, mesangial cells, and tubular epithelial cells. However, in a following study, selective MC1R agonists barely induced any cAMP response in podocytes58. The doubt on podocyte expression of MC1R as well as MC1R-mediated podocyte protection was further accentuated by the contradictory effects of MC1R agonists on proteinuria and podocyte injury observed in different animal models of glomerulopathies59.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, MC1R agonists protect against apoptosis and has been shown to lower proteinuria. 29,30 Systemic immunomodulation through MCR and anti-inflammatory effects on peripheral white blood cells through MCR 1, 3, and 5 may be other mechanisms by which ACTH exerts its effects. 31,32 ACTH gel was overall well-tolerated over 6 months, with reversible polycythemia in 1 patient and 6 infections, none resulting in hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that MC1R promotes increases stressfibers in podocytes and protects from PAN damage by activating RhoA 14 . PAN damage is a slow process (i.e.…”
Section: Resultsmentioning
confidence: 81%
“…First, we showed that activation of the epidermal growth factor receptor (EGFR) resulted in increase of Rac1 and loss of stressfibers in podocytes 13 . Secondly, we showed stress fiber protection from puromycin aminonucleoside (PAN) damage by MC1R activation resulting in regulation of the redox status of the cells and induction of stressfibers through RhoA 14 .…”
Section: Introductionmentioning
confidence: 96%